Omega-3 Status and the Relationship between Plasma Asymmetric Dimethylarginine and Risk of Myocardial Infarction in Patients with Suspected Coronary Artery Disease - Heidi Borgeraas; Elin Strand; Eva Ringdal Pedersen; Jutta Dierkes; Per Magne Ueland; Reinhard Seifert; Eirik Rebnord Wilberg; Pavol Bohov; Rolf K. Berge; Dennis W. T. Nilsen; Ottar Nygård (Cardiology Research and Practice, 2012)
Background. Asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of nitric oxide synthase. A previous rat study revealed an ADMA lowering effect following treatment with omega-3 polyunsaturated fatty acids (n-3 PUFAs). We sought to examine if an association between plasma ADMA and risk of acute myocardial infarction (AMI) was modified by serum n-3 PUFA status. Methods. The cohort included 1364 patients who underwent coronary angiography for suspected coronary artery disease in 2000-2001. Fatal and nonfatal AMI events were registered until December 31, 2006. Risk associations with AMI were estimated across ADMA quartiles (linear trend) and the upper decile. Results. No association between concentration of any n-3 PUFA and ADMA was observed. Only ADMA levels in upper decile were significantly associated with AMI with a multivariate adjusted hazard ratio (HR) (95% confidence interval) versus the rest of the population of 2.11 (1.34, 3.32). The association was strengthened among patients with below median levels of α-linolenic acid (ALA) (HR 3.12 (1.64, 5.93)), but was only influenced by longer chain n-3 PUFA after additional adjustments for HbA1c, estimated glomerular filtration rate, and hypercholesterolemia. Conclusions. The association of ADMA with risk of AMI is influenced by serum n-3 PUFA and particularly ALA.